FORMULASI SEDIAAN GRANUL EFFERVESCENT SARI BUAH SIRSAK (Annona muricata L) - Burhan, Lisma; Yamlean, Paulina V. Y.; Supriati, Hamidah Sri (UNIVERSITAS SAM RATULANGI, 2012)
Soursoup fruit nutrient includes vitamins C and B1. Vitamin which is the most dominant insoursop fruit is vitaman C, where the compound is in the form of a natural antioxidant in thebody. Antioxidants help the body to fight against various free radicals that enter the body and isexcellent for improving the immune system and slow the aging process. This study aimed toinvestigate the effect of different formulations of effervescent granules made from soursoup fruitjuice against physical properties of granules prepared by wet granulation method. Testpreparation includes organoleptic quality, moisture content, flow properties, and solubility time.Of the three formulations, variations in the quantity of citric acid, tartaric acid and sodiumbicarbonate gave effect on water levels, silence angle, and time of depression of granule made ofsoursoup fruit juice. In formulation 1, the water content was 0.19%, a flow rate of 8.2 seconds,the silence angle of 33.02 degrees, and dispersion time was 2 minutes 13 seconds.In the secondformulation, water content was 0,21%, a flow rate of 8.1 seconds, the silence angle of 31.52degrees, and dispersion time at 3 minutes 3 seconds. In the third formulation, water content was0,28%, a flow rate of 9,7 seconds, the silence angle of 31.56 degrees, and dispersion time at 4minutes 5 seconds.Key words: soursoup, effervescent granule, wet granule, natrium bicarbonate